The relationship between patient characteristics and analgesic self-medication behavior in pharmacies in Kesesi District, Pekalongan Regency - hilmiyah, Rahmah (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Self-medication is an effort to self-medicate without a doctor's prescription. Analgesics are medications used to reduce or relieve pain. The purpose of this study was to determine the relationship between patient characteristics and analgesic self-education behavior in pharmacies in Kesesi District, Pekalongan Regency. This study used an analytical observational method with a cross-sectional approach, the research instrument used a questionnaire involving 97 respondents in 3 pharmacies in Kesesi District, Pekalongan Regency. The sampling technique uses the consecutive sampling method. The independent variable is the characteristic and the dependent variable is the analgesic self-medication behavior. Data analysis using univariate and bivariate analysis with non-parametric rank spearman statistical test. The results showed that the age of 26-45 years was 50.5%, women were 66%, secondary education was 61.9%, self-employed by 47.7% and 32% of moderate-income people were more self-medicated analgesics. Some patients had good behavior in self-medication analgesics by 71.1%. The conclusion of this study was that patient characteristics including age (p = 0.014), education (p = 0.000), occupation (p = 0.000) and income (p = 0.000) had a relationship with analgesic self-medication behavior in pharmacies Kesesi District, Pekalongan Regency, while unrelated patient characteristics were gender (p = 0.237).